DECAY PARAMETERS OF AFTERSHOCK SEQUENCES GLOBALLY DISTRIBUTED - Tsapanos, T.M.; Koravos, G. Ch.; Plessa, A.; Vythoulkas, N.K.; Pitsonis, I.S. (Bulletin of the Geological Society of Greece, 2010)
The evaluation of the parameters c and k of the decay law of the aftershocks in an earthquake sequence has been carried out in this study. For this reason 170 seismic sequences globally distributed, during the time period 1964-1986, were performed. All of them modelled well by Omori’s law. We estimated that the mean global values of and parameters , are 0.660+0.181 and - 0.341+0.090, respectively. The values of these parameters are also estimated for different regions of the world, west and east part of circum-Pacific rim, as well as for the Eurasia belt.The parameters c and k calculated for the various regions of the world found to be spread around the global average, although admittedly few exceptions to this generalization are also observed to exist.